The Role of the Maqasid Approach as a Key Instrument in Qur'anic Tadabbur in the Contemporary Era - Elenia, Stevani (Universitas Islam Internasional Darullughah Wadda'wah, 2025)
Tadabbur Al-Qur'an is a term that describes the process of understanding, contemplating, and internalizing the contents of the Quran. This process requires an in-depth analysis of the divine revelation that is not only textual but also exploratory. However, in practice, tadabbur is often carried out without a systematic approach, resulting in a partial and less contextual understanding. In this regard, Maqasid Al-Qur'an, which is one of the approaches to revealing the intended meaning of the Quranic verses, serves as a crucial instrument in tadabbur to achieve a more comprehensive and relevant understanding of the Quranic teachings in contemporary life. This study aims to analyze the role of Maqasid Al-Qur'an in tadabbur to achieve a more holistic understanding of the Quranic teachings. This study employs a qualitative approach with literature analysis, focusing on primary sources in tafsir, Maqasid Al-Qur'an, and tadabbur. The data is analyzed using descriptive-analytical methods to explore the role of Maqasid in the tadabbur process. The findings of this study indicate that the Maqasid approach makes tadabbur more systematic and contextual, facilitating a deeper understanding of the spiritual, social, and moral values of the Quran. Furthermore, this study emphasizes that understanding based on Maqasid provides more relevant insights in addressing modern challenges. This study contributes to strengthening the integration between Maqasid Al-Qur'an and tadabbur, which can serve as a systematic approach in Quranic interpretation.